RNA binding protein POP7 regulates ILF3 mRNA stability and expression to promote breast cancer progression. Issue 11 (6th September 2022) - Huang, Yanni; Zheng, Yizi; Yao, Ling; Qiao, Feng; Hou, Yifeng; Hu, Xin; Li, Daqiang; Shao, Zhiming
Abstract: RNA binding proteins (RBPs) play pivotal roles in breast cancer (BC) development. As an RBP, Processing of precursor 7 (POP7) is one of the subunits of RNase P and RNase MRP, however, its exact function and mechanism in BC remain unknown. Here, we showed that expression of POP7 was frequently increased in BC cells and in primary breast tumors. Upregulated POP7 significantly promoted BC cell proliferation in vitro and primary tumor growth in vivo. POP7 also increased cell migration, invasion in vitro, and lung metastasis in vivo. Through RNA immunoprecipitation coupled with sequencing (RIP‐seq), we found that POP7 bound preferentially to intron regions and POP7‐binding peak associated genes were mainly enriched in cancer‐related pathways. Furthermore, POP7 regulated Interleukin Enhancer Binding Factor 3 (ILF3) expression through influencing its mRNA stability. Knockdown of ILF3 significantly impaired the increased malignant potential of POP7‐overexpressing cells, suggesting that POP7 enhances BC progression through regulating ILF3 expression. Collectively, our findings provide the first evidence for the important role of POP7 and its regulation of ILF3 in promoting BC progression. Abstract : Our findings provide the first evidence for RNA‐binding protein POP7 in promoting breast cancer progression. Through RIP‐seq, we found that POP7 bound preferentially to intron regions of target RNAs and ILF3 was identified as one of the POP7‐binding transcripts. And regulation of ILF3 expression and mRNA stability is through which POP7 exerts its function on promoting breast cancer.